ChemInform Abstract: A Convenient ′NOSE′ Approach Used Towards the Synthesis of 6‐Amino‐1, 3‐dimethyl‐5‐indolyl‐1H‐pyrimidine‐2, 4‐dione Derivatives Catalyzed by Nano‐Ag. Issue 29 (June 2016) - Das, Vijay Kumar; Bharali, Pranjal; Konwar, Bolin Kumar; Mikkola, Jyri‐Pekka; Shchukarev, Andrey; Thakur, Ashim Jyoti
Abstract: Uracil‐based compounds are efficiently synthesized in good to high yields under aerobic conditions using moisture‐stable and recyclable nano‐Ag as catalyst.